A atitude budista diante da sexualidade dissidente e o surgimento contemporâneo de comunidades budistas LGBTI+ como movimento socialmente engajado - Matias, Ícaro Azevedo (2023)
The present work is the result of an analysis on Buddhism's attitude towards people of dissident sexuality and gender deviance throughout history. That is, it evaluated how this religion created specific norms for different sexualities; how it explained the sexual diversity of human beings, and what place it determined for LGBTI+ people in the religious community. From this understanding, it then examined the emergence of LGBTI+ Buddhist communities as a form of Socially Engaged Buddhism. To achieve the research objectives, a literature review was conducted considering the intersection between Buddhism, sexuality, and gender within the LGBTI+/queer cut. In addition, a documentary research was carried out selecting content produced by three different communities (Rainbow Sangha Europe, Rainbodhi Australia and Rainbow Sangha Brazil) in order to understand the identity and character of these groups' activities. With this, LGBTI+ Buddhist communities were evaluated under the aegis of an analytical category called Socially Engaged Buddhism, with specific criteria and parameters. As a result, the work found a flexible attitude of Buddhism, with traces of neutrality that allowed for different interpretations and stances towards sex/gender diversity. This ambivalence gave opportunity for the development of religious leadership and communities of LGBTI+ practitioners that assumed a character of social engagement, with specific agency justified as Buddhist practice and action in secularized public spaces